Swedish Exodus - Ljungmark, Lars (Book collections on Project MUSE., 1996)
""America fever"" gripped Sweden in the middle of the nineteenth century, seethed to a peak in 1910, when one-fifth of the world's Swedes lived in America, cooled during World War I, and chilled to dead ash with the advent of the Great Depression in 1930.Swedish Exodus, the first English translation and revision of Lars Ljungmark's Den Stora Utvandringen, recounts more than a century of Swedish emigration, concentrating on such questions as who came to America, how the character of the emigrants changed with each new wave of emigration, what these people did w.